Fundo de garantia de alimentos devidos a menores no contexto do estado social - Diogo, Joana Maria Costa Leal (2018)
The child support is part of the core of the parental responsibility, with the parents' duty to provide for the maintenance of their children, as a means of ensuring their dignity and survival during the minority and, in special situations, after reaching the age of majority, fulfilling the constitutional guarantee of article 24th of the CRP. The biggest problem with this issue arises when the parents do not fulfill the obligation of food, leaving the children unprotected and even more fragile. As these situations become more and more frequent, the question arises as to how the dignity and survival of these children are ensured, whether existing legislation is sufficient to protect those who are most fragile, whether the principle of equality is not ensured, when the parents fail to do so. In order to overcome this lack of compliance on the part of the failing parent, the Portuguese State, in order to guarantee or try to guarantee the dignity of these children, created the FGADM, which can only be understood through the analysis of parental responsibilities. For de fund to intervene it is necessary that the following conditions are met (law 75/98, and DL 164/99): 1. There must be a fault in the child support’s payment; 2. The maintenance creditor should reside in national territory; 3. There is an inability to use the article 48º RGCTP procedure; 4. The creditor does not have an income exceeding 428,90 euros (IAS) or not benefit to the same extent of another income from the parent who hashis custody. The question on which we will focus mainly on this dissertation will be to see if the value determined by the Court in charge of the FGADM must be of a lower amount, equal or superior to that which would be assigned to the missing parent, also focusing on the Uniform Judgment of Jurisprudence of March 19, 2015, which from the perspective adopted does not fulfill the concepts of need of the minor, nor equality, promoting in certain situations a true inequality.